The Abiotic parameters and its relationship with phytoplankton abundance off Puerto López (2011-2012), Province of Manabí, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2015)
This study evaluated the impact of abiotic parameters in phytoplankton abundance at standard depths of the water column at a station located 10 miles off Puerto López in 2011 and 2012. A taxonomic identification and quantification of phytoplankton species were performed as well as the temperature and inorganic nutrients were recorded. Phytoplankton featured variationsin abundance and distribution, being its values the lower registered for this area with increased cell activity between the surface and 10 m depth, being Nitzschia longissima and Cylindrotheca closterium, typify the phytoplankton community in terms of abundance and permanence registered. The results were validated statistically by: Kruskal-Wallis nonparametric test, canonical correspondence analysis and Spearman rank correlation. The relationships between the phytoplankton and existing oceanographic conditions determined that species Dactyliosolen fragilissimus, Pseudo-nitzschia seriata complex and Leptocylindrus danicus had a strong correlation with the nutrients (nitrite, nitrate and silicate) , the second and third nutrient showed positive influence in the growth of L. danicus in 2011, while for 2012 Cylindrotheca closterium and Pseudo-nitzschia seriata complex and showed strong inverse correlation with temperature and direct with nutrients, specifically strong with nitrite and strong with nutrients, that’s to say, that environmental variables influenced the abundance of phytoplankton.
Keywords: seasonality; water column; La Niña; diatoms; Nitzschia longissima